The Drivers of Pathology in Zoonotic Avian Influenza: The Interplay Between Host and Pathogen - Horman, William S. J.; Nguyen, Thi H. O.; Kedzierska, Katherine; Bean, Andrew G. D.; Layton, Daniel S. (Frontiers in Immunology, 2018)
The emergence of zoonotic strains of avian influenza (AI) that cause high rates of mortality in people has caused significant global concern, with a looming threat that one of these strains may develop sustained human-to-human transmission and cause a pandemic outbreak. Most notable of these viral strains are the H5N1 highly pathogenic AI (HPAI) and the H7N9 low pathogenicity AI (LPAI) viruses, both of which have mortality rates above 30%. Understanding of their mechanisms of infection and pathobiology is key to our preparation for these and future viral strains of high consequence. AI viruses typically circulate in wild bird populations, commonly infecting waterfowl and also regularly entering commercial poultry flocks, with live poultry markets providing an ideal environment for the spread AI and potentially the selection of mutants with a greater propensity for infecting humans. Pathology from these infections is primarily driven by a dysregulated immune response, which is characterised by systemic spread of the virus, resulting in lymphopenia and hypercytokinemia. It has been well documented that host/pathogen interactions, particularly molecules of the immune system, play a significant role in both disease susceptibility as well as disease outcome. Here we review the immune/virus interactions in both avian and mammalian species, and provide an overview or our understanding of how immune dysregulation is driven. Understanding these susceptibility factors is critical for the development of new vaccines and therapeutics to combat the next pandemic influenza.